Two new epiphytic species of Impatiens L. (Balsaminaceae) from the southern Western Ghats, India - Saravanan, Thokuluva Santharam; Kaliamoorthy, Seventhilingam (Phytotaxa, 2022)
Two new epiphytic species of Impatiens L. (Balsaminaceae), viz., Impatiens keralensis and Impatiens kurichiarmalayana are described from Wayanad district, Kerala, India. Impatiens keralensis is allied to I. modesta Wight and I. mohana Ratheesh, Sujana & Anil Kumar; and Impatiens kurichiarmalayana is to I. mankulamensis K. M. P. Kumar, R. Jagad. & Nagaraj and I. panduranganii K. M. P. Kumar, R. Jagad. & G. Prasad. The newly described taxa are readily distinguishable from their allied species by unique character combinations viz., leaf size, leaf, margin, lateral sepal, lower sepal, dorsal petal, wing petal and seeds. Detailed descriptions along with photographs and comparison tables are provided.